PENDIDIKAN ISLAM GLOBAL: KAJIAN DESKRIPTIF ANALITIS - Saekhudin Zuhri (Risâlah, Jurnal Pendidikan dan Studi Islam, 2018)
Education is a conscious and planned effort to create an atmosphere of learning and learning process so that learners actively develop their potential to have spiritual strength, self-control, personality, intelligence, noble character, and skills needed himsef, society, nation and state.Islam is a religion that has a comprehensive concept of doctrine, profound and comprehensive. Islam is submissive, obedient, implementation and reward. Global is the result of a change (evolution) of public relations that brings a new awareness of relationships or interactions between people. Global Islamic Education is a conscious and planned effort to realize, realizing the learning atmosphere and the learning process of Islamic Religion universally covers the whole world and open to the ummah. The purpose of Islamic education is to humanize human effort. In order for Islam to be meaningful to the global community and to build a great generation, Islam is expected to come up with the following nuances: Islam is friendly, tolerant, fiddy, critical, creative, collaborative, innovative and best performance. Keywords: Education, Islam, Global